A família do portador de sofrimento psíquico e os serviços de saúde mental: Estudo de caso - Moreno, Vânia[UNESP]; Bucchi Alencastre, Márcia (Universidade Estadual de Maringa, 2004)
This qualitative research, case study type, aimed at presenting the understanding of psychic sufferers in search for mental health services during emergency situation, partial hospitalization or in ambulatory services. 12 family members were interviewed. They reported difficulties in the attendance in the emergency room when the patient is in crisis, as well as doctors considering merely the present symptomatology and undervaluing their own knowledge of the sickening process. The day-care hospital is conceived as a place to provide care, occupation and should teach as a school. The ambulatory service represents for the family the possibility of the patient being responsible for their attendance to the consultations and for the correct use of the medication.
Families of psychic sufferers and mental health services: A case study
Keywords: Family; Health services; Mental disturb; Psychic sufferer; ambulatory care; case study; consultation; day care; emergency care; emergency ward; family relation; hospitalization; human; human experiment; mental disease; mental health service; occupation; patient compliance; qualitative research